2010
DOI: 10.1161/circulationaha.109.924068
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Lead V 1 ST Elevation During Acute Inferior Myocardial Infarction

Abstract: Occlusion-2 (HERO-2) trial, V 1 ST levels were analyzed with adjustment for lead V 3 ST level for predicting 30-day mortality. V 1 ST elevation at baseline, analyzed as a continuous variable, was associated with higher mortality. Unadjusted, each 0.5-mm-step increase in ST level above the isoelectric level was associated with Ϸ25% increase in 30-day mortality; this was true whether V 3 ST depression was present or not. The odds ratio for mortality was 1.21 (95% confidence interval, 1.07 to 1.37) after adjustme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In this project ST segments are identified by location of the R-peak. According to the information obtained from references ( 15 , 16 ) in 250 Hz sampling frequency, the ST segment appears after the end of the QRS complex in a 120 mS window with 30 sample lengths. This method makes it possible to achieve the ST segment in the application of real time processing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this project ST segments are identified by location of the R-peak. According to the information obtained from references ( 15 , 16 ) in 250 Hz sampling frequency, the ST segment appears after the end of the QRS complex in a 120 mS window with 30 sample lengths. This method makes it possible to achieve the ST segment in the application of real time processing.…”
Section: Methodsmentioning
confidence: 99%
“…ST segment elevation is one of the earliest signs of heart attack. According to reliable reports ( 15 , 16 ) when this piece is higher than 0.1 mV, it is called ST-elevation.…”
Section: Methodsmentioning
confidence: 99%
“…6 Data from the Hirulog and Early Reperfusion or Occlusion-2 trial showed that ST segment elevation of 1 mm or greater in lead V 1 is associated with an increased risk of death in patients with acute inferior myocardial infarction. 7 Furthermore, the presence of ST-segment elevation in lead V 6 in patients with acute Q-wave inferior myocardial infarction, as evident in the first electrocardiogram, is associated with larger infarct size and a greater incidence of major arrhythmias. 8 ■ Determining the culprit vessel…”
Section: Qmentioning
confidence: 99%
“…Clinically, the surface 12-lead electrocardiogram (ECG) test is still one of the most commonly used methods of the initial screening of CAD due to its nature of non-invasiveness, low cost, and timeliness [4], [5]. Certain morphologic ECG abnormalities, including T-wave inversion, abnormal Q-wave, and STsegment depression or elevation, have proved their clinical significance in risk stratification [6][7][8] and associations with myocardial ischemia and infarction [9][10][11][12][13][14]. However, these abnormalities are nonspecific symbols of CAD and can be observed in non-cardiac conditions, such as central nervous system diseases, hypothermia, and pulmonary embolism [15].…”
Section: Introductionmentioning
confidence: 99%